A large-scale transcontinental river system crossed West Antarctica during the Eocene - Zundel, Maximilian; Spiegel, Cornelia; Mark, Chris; Millar, Ian; Chew, David; Klages, Johann; Gohl, Karsten; Hillenbrand, Claus-Dieter; Najman, Yani; Salzmann, Ulrich; Ehrmann, Werner; Titschack, Jürgen; et al. (Science advances, 2024)
Extensive ice coverage largely prevents investigations of Antarctica’s unglaciated past. Knowledge about environmental and tectonic development before large-scale glaciation, however, is important for understanding the transition into the modern icehouse world. We report geochronological and sedimentological data from a drill core from the Amundsen Sea shelf, providing insights into tectonic and topographic conditions during the Eocene (~44 to 34 million years ago), shortly before major ice sheet buildup. Our findings reveal the Eocene as a transition period from >40 million years of relative tectonic quiescence toward reactivation of the West Antarctic Rift System, coinciding with incipient volcanism, rise of the Transantarctic Mountains, and renewed sedimentation under temperate climate conditions. The recovered sediments were deposited in a coastal-estuarine swamp environment at the outlet of a >1500-km-long transcontinental river system, draining from the rising Transantarctic Mountains into the Amundsen Sea. Much of West Antarctica hence lied above sea level, but low topographic relief combined with low elevation inhibited widespread ice sheet formation.